2018
DOI: 10.1016/j.tsf.2018.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of angle deposition γ on the structural, optical and electrical properties of copper oxide zigzag (+γ, −γ) nanostructures elaborated by glancing angle deposition

Abstract: In this work, Cu x O thin films were obtained by air annealing of copper thin films deposited on glass substrates using thermal evaporation method by Glancing Angle Deposition "GLAD" technique. The copper was sculptured into a zigzag shape, which presents two columns with inclined angles + and-where is the deposition angle between the incident flux and the substrate normal. Morphological, structural, optical and electrical properties of the obtained thin films were investigated using X-ray diffraction (XRD), U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…To evaluate the influence of the pH on the Cu2O electrodeposition, we characterized the electrodeposited Cu2O nanostructures by XRD. Figure 3 shows that the resulting materials exhibit 5 narrow and sharp peaks at 2θ values of 29.56°, 36.47°, 42.40°, 61.39°, and 73.57°, corresponding to (110), ( 111), ( 200), (220), and (311) planes, respectively, thus confirming the successful synthesis of a cubic phase crystal form of Cu2O which is in perfect agreement with JCPDS card No 01-078-2076 [33,34]. No corresponding peak to copper oxide or metallic copper peak is observed.…”
Section: Structural Characterizationsupporting
confidence: 81%
See 1 more Smart Citation
“…To evaluate the influence of the pH on the Cu2O electrodeposition, we characterized the electrodeposited Cu2O nanostructures by XRD. Figure 3 shows that the resulting materials exhibit 5 narrow and sharp peaks at 2θ values of 29.56°, 36.47°, 42.40°, 61.39°, and 73.57°, corresponding to (110), ( 111), ( 200), (220), and (311) planes, respectively, thus confirming the successful synthesis of a cubic phase crystal form of Cu2O which is in perfect agreement with JCPDS card No 01-078-2076 [33,34]. No corresponding peak to copper oxide or metallic copper peak is observed.…”
Section: Structural Characterizationsupporting
confidence: 81%
“…The structural characterizations of the electrodeposited Cu2O nanostructures at different applied potentials are presented in Figure 7. XRD peaks of the electrodeposited Cu2O films are assigned to the cubic phase with miller indices (110), ( 311), ( 200), (220), and (111) planes, respectively (JCPDS card N°: 01-078-2076) [51,52]. These peaks are narrow and sharp indicating that Cu2O films presented a good crystalline, and their intensity increases as the deposition potential increases.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…The obtained results were consistent with the results of other researchers. In [50], Chaffar Akkari et al described the fabrication of CuO x films on glass substrate by air annealing copper thin films deposited by thermal evaporation method using the GLAD technique. In this work, the morphological, structural, optical, and electrical properties were measured.…”
Section: Introductionmentioning
confidence: 99%
“…Most cases of elaboration of such films are by vacuum thermal evaporation, sputtering, or e-beam. In previous works, it has been shown that the GLAD technique is able to create optical, electrical or magnetic anisotropy because of the highly oriented nanostructures [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%